Identifying High-alert Medications in a University Hospital by Applying Data From the Medication Error Reporting System. Issue 6 (September 2021) - Tyynismaa, Lotta; Honkala, Anni; Airaksinen, Marja; Shermock, Kenneth; Lehtonen, Lasse
Abstract : Objectives: To facilitate safe use of high-alert medications, lists of medications posing higher risks for medication errors (MEs) and harmful effects have been compiled. These lists can be general or reflect clinical practices in specific settings. Less common has been to compile a hospital-specific list applying data from the organization's ME reporting system. Our objective was to demonstrate a method for compiling such a high-alert medication list in a university hospital. Methods: Of the eighteen 136 MEs reported during 2007 to 2013, ME reports with medications coded as a contributing factor to the incident were included (n = 249). The involved medications were identified and compared with the hospital's drug consumption and Institute for Safe Medication Practice's List of High-Alert Medications. The report narratives of MEs with most reported and high-alert medications (120 reports) were qualitatively content analyzed. Results: The included 249 reports concerned 280 medications, of which 33% were classified as high-alert medications by the Institute for Safe Medication Practice. The most common therapeutic groups were antibacterials for systemic use (13%), psycholeptics (10%), analgesics (9%), and antithrombotic agents (9%). The most common high-alert medications were oxycodone (5%), enoxaparin (3%), and noradrenaline (3%). Serious patient harm (3%) was related to cefuroxime, enoxaparin, ibuprofen, midazolam, propofol, and warfarin. A half of the MEs were related to parenteral preparations. The qualitative content analysis revealed the key process safety risks of the most reported and high-alert medications. Conclusions: The method is applicable for compiling a hospital-specific high-alert medication list and related analysis of key process safety risks contributing to MEs.